PENDAMPINGAN MASYARAKAT SEMBALUN LAWANG DALAM PENANAMAN SAYURAN BAYAM BRAZIL SECARA ORGANIK MENUJU PERTANIAN BERKELANJUTAN - Thei, Ruth Stella Petrunella; Rifqi, Afif Aufa; Husni, Ika Rauhul; Wardani, Intan Siwi Kusuma; Yuliana, Sari; Hidayati, Laela Asri; Rosyada, Laila Amrina; Hijaratullah, Imam Hanif; Sasmita, Siti Soleha; Fansuri, Haikal; Majid, Azriel Akbar Hermansyah (Jurnal Wicara, 2023)
The climate and regional conditions in Sembalun Lawang Village make it possible to cultivate various types of plants, both types of food crops and horticultural crops. Problems that are often encountered in crop cultivation are pests and diseases that damage cultivated plants, especially for horticultural crops. The use of chemical pesticides is a mainstay of farmers in dealing with pests and diseases. On the other hand, the use of chemical pesticides threatens environmental health. In addition, the stunting rate is also one of the problems in Sembalun Lawang Village. The solution that can be offered is the cultivation of Brazilian spinach organically, namely using compost, seeing that this Brazilian spinach cultivation technique does not require extra care so that it can minimize the use of chemical fertilizers and pesticides. Apart from that, Brazilian spinach has many benefits, one of which is that it contains magnesium which is good for bone growth and is good for preventing anemia. Then this Brazilian spinach can also be processed into various processed products that can be consumed by children such as porridge, pudding, smoothies and others which can reduce stunting rates. Apart from processed products that are consumed by children, there are also processed products that can be developed and become new businesses such as Brazilian spinach chips. Therefore, counseling activities on Brazilian spinach cultivation and the manufacture of preparations from Brazilian spinach are one of the things that must be done with the aim of increasing public knowledge and awareness so that they are wiser in using chemical fertilizers and pesticides and opening up opportunities for villagers to open new businesses. from processed Brazilian spinach. This activity was carried out on July 14th and 26th 2023 at Sembalun Lawang Village Office. This activity was attended by Sembalun Lawang Village officials, farmers, female cadres in each hamlet, and mothers with stunted children. This activity is carried out through lecture methods and direct demonstrations. The results of the training show that the community is interested in cultivating Brazilian spinach and interested in making processed products from Brazilian spinach.